The impact of COVID-19 on the doctor-patient relationship in China - Bo Xu (Frontiers in Public Health, 2022)
A strong doctor-patient relationship (DPR) is crucial to the effectiveness of treatment. It is imperative to maintain a good DPR during treatment. During 2019, Coronavirus Disease 2019 (COVID-19) brought new challenges to already difficult doctor-patient relationships. This paper summarized the current state of the DPR, compared the changes between China and other countries after the outbreak of COVID-19, and listed the solutions proposed by various countries. Finally, the author suggested some solutions in order to improve the DPR according to China's own circumstances.